Patients with positive HER-2 amplification advanced gastroesophageal junction cancer achieved complete response with combined chemotherapy of AK104/cadonilimab (PD-1/CTLA-4 bispecific): A case report - Peng, Jieqiong; Zhu, Qiang; Peng, Ziru; Chen, Zhen; Liu, Yuantao; Liu, Bo (Frontiers in Immunology, 2022)
Background: Human epidermal growth factor receptor 2(HER2) is the most prominent therapeutic target for advanced gastric (G)/GEJ cancer. However, targeted therapy did not significantly improve survival. Currently, there are no regimens for the treatment of HER-2 amplification that exempt targeted agents. Case Presentation: A 42-year-old man was diagnosed with adenocarcinoma of GEJ (IV): liver metastasis, lung metastasis. The patient was enrolled in a trial that excluded with known HER2-positivity: AK104, a PD-1/ CTLA-4 bispecific antibody, combined with chemotherapy (mXELOX) as first-line therapy for advanced gastric G/GEJ cancer (NCT03852251). After 6 cycles of AK104 combined with chemotherapy therapy, immune-related pulmonary toxicity was observed. We rechallenged AK104 after hormone therapy and no further pulmonary toxicity was observed. Immunerelated hepatitis occurred in the patient during immunotherapy combined with single-drug capecitabine therapy. After combined steroid therapy with mycophenolate mofetil, the patient's immune hepatitis improved. Nevertheless, thepatient was excluded from the clinical study due to the long-term absence of medication. Antitumor therapy was also discontinued in view of the patient's adverse immune response. The patient did not receive subsequent immune antitumor therapy, and immune-related hepatitis still occurred intermittently, but the disease evaluation maintained to PR. Complete response was confirmed by PET/CT and the biopsy specimen from gastroscopy on 2020-06-10. Next generation sequencing of biopsy tissue to guide subsequent therapy at a recent follow-up visit. The results indicated that ERBB2 mutations; copy number 58.4934(HER-2), TMB=3.1, MSS. IHC: EBV(-),PD-L1 CPS=3,HER-2 (3 +). Conclusions: Patients with HER-2 positive advanced GEJ cancer received PD-1/ CTLA-4 bispecific immunotherapy combined with chemotherapy and achieved complete remission. It offers a novel, highly specific and highly potent therapeutic option for HER-2 positive patients. Its use should be considered a new treatment when trastuzumab is not viable. Currently in development to overcome this resistance.